Beneficial Effect Of Tamarindus Indica On The Testes Of Albino Rat After Fluoride Intoxication - P.K. SINGH; FEROZ A.D.; SHEEBA H.; KHALIL A; SAMIR A.M (International Journal of Pharma and Bio Sciences, 2012)
The Present investigation covers the scientific comprehension of the potential effects of fluoride toxicity on body and testes weight and the spermatozoal activities in male albino rat and the beneficial effect of novel medicinal plant Tamarindus indica therapeutic treatment (10gm/kg body weight) after fluoride water intoxication. Three groups of male albino rats five of each were intoxicated with ground water fluoride (14.29 mg/L fluoride ion concentration) collected from fluoride zone of Agra. The other three groups were given the subsequent treatment of Tamarindus indica after fluoride water intoxication. The fluoride water exposure led to the significant reduction in the body and organ weight, whereas the sperm count, motility and sperm sluggishness were the decline of sperm count and its activities. However, the therapeutic treatment of Tamarindus indica pulp extract manifested the improvement in the recovery and mitigation of devastating toxic effects of fluoride on the concerned parameters in male albino rat.